The Effectiveness of The RME Approach on Mathematics Learning Outcomes in Statistics for Junior High School Students in Palu City - Salsabila Aski; Rahma Nasir; Mustamin Idris; Bakri Mallo (JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to determine the effectiveness of the RME (Realistic Mathematics Education) approach on the learning outcomes of eighth-grade students in statistics. This is a quantitative study using a quasi-experimental design with a pretest-posttest control group. The population of this study consists of eighth-grade students at SMP Labschool UNTAD Palu, comprising four classes with a total of 100 students. A sample of 50 students was selected using random sampling. The data collection methods used were learning outcomes from essay-based tests and observations. The data analysis techniques used were the independent samples t-test and the N-Gain test. The results of the independent samples t-test showed a Sig. (2-tailed) value of 0.001, indicating a significant difference in learning outcomes between the experimental and control classes. The N-Gain Score calculation for the experimental class yielded a value of 0.66, which falls into the moderate category. Therefore, it can be concluded that the RME approach is effective in improving the learning outcomes of eighth-grade students in statistics. The effectiveness of the RME approach is supported by learning stages that link mathematical concepts to real-life situations, enabling students to build understanding and deepen their grasp of statistical concepts, thereby improving their learning outcomes. Keywords: Effectiveness, RME, Learning Outcomes